FINANCIAL RISK ASSESSMENT OF ALBANIAN SMEs WITH THE HELP OF FINANCIAL RATIOS ( A CASE STUDY– SME-S IN GJIROKASRA REGION) - Kociu, Lorenc; Mano, Romeo; Hysi, Armand (European Scientific Journal, ESJ, 2015)
The purpose of this work is to assess financial risk, facing Albanian SMEs. The study is focused on the analysis of financial ratios issued by the Balance Sheet, Statement of Income and Expenses, Cash Flow of SMEs operating in the region of Gjirokastra, for the period 2009 - 2013, through which is assessed the capital structure risk, the liquidity risk and the insolvency risk. For the assessment of financial risk financial data are processed with statistical software SPSS version 21, using a linear regression model. Through this analysis, is going to be identified which elements have the greatest impact of financial risk and which steps the bussinesses should follow to reduce negative risk or to improve a positive ones.